LEGAL STANDING STATE OWNED ENTERPRISES DALAM INTERNATIONAL CENTRE FOR SETTLEMENT OF INVESTMENT DISPUTES (ICSID): IMPLEMENTASI BROCHES TEST DALAM BEIJING URBAN CONSTRUCTION GROUP, CO., LTD. V. REPUBLIC OF YEMEN (ICSID CASE NO. ARB/14/30) - Christofer Lucky; Cut Memi (Fakultas Hukum Universitas Tarumanagara, 2019)
The development of the world of arbitration as one of the ways to resolve non-litigation disputes today is quick as thought. The International Centre for Settlement of Investment Disputes (ICSID) is an international arbitration centre focus solely on the settlement of investment disputes between State and National of Another Contracting State. However, the rapid development of economic growth in foreign direct investment brought new legal jurisdiction to ICSID regarding Chinese State Owned Enterprises. For this purpose, a formula by Aron Broches was set as a test for any State Owned Enterprises that wishes to bring their case before ICSID Arbitration. The so called Broches Test is now in questioned, as to the peculiar case in BUCG v. Yemen, where the test itself is collided with the fact that more than 300 Chinese State Owned Enterprises is investing with commercial nature but bringing the China policy on Belt and Road Iniative.